The Environment of Awakening: Dream Incubation, Spiritual Maturation, and the Local Church - Packer, Charles A. (International congregational journal, 2019)
Ancient sources, including several instances in the biblical witness, attest to the practice of dream incubation, in which encounter with the deity through the medium of dreaming is facilitated by placing oneself in a particularly sacred or significant location and sleeping. The goal is to receive a potentially life-changing message in that space. In a time in which calls to ministry are increasingly rare and in which theological seminaries, the historical locus of education for formal Christian service, are closing, merging, or geographically relocating, the Congregational tradition with its emphasis on the local church and the importance of the meetinghouse as a site for the community to gather, is uniquely poised to encourage such transformative dreaming and awakening to both general and specifically Christian vocation. Further, the local church is the context in which the gifts of the individual who perceives such a summons might be tested and tried, as well as where skill development, spiritual maturity, and practical development might occur. This study will draw on both historic and contemporary sources, including Horace Bushnell and James Fowler, as well as examine the role of the Congregational meetinghouse and the possibilities of nurturing future ministry.